Community blood lead survey with emphasis on preschool children following lead dust pollution in Esperance, Western Australia - Enrico Rossi; Virginia McLaughlin; John Joseph; Max Bulsara; Kerryn Coleman; Charles Douglas; Andrew Robertson (Elsevier, 2012)
Abstract Objective: To assess the impact of airborne lead dust on blood lead levels in residents of Esperance, a regional Western Australian town, with particular reference to preschool children. Methods: Following identification of significant airborne lead contamination, residents were notified that a blood lead clinic was available to all, with testing of preschool children encouraged. About 40% (333 children) of the preschool group and about 20% of the remaining population were tested. The main measures were blood lead levels, prevalence of elevated results and comparisons to other Western Australian surveys. Results: In preschoolers, 2.1% (seven children) had blood lead levels exceeding the current 10 μg/dL level of concern. This was not significantly different to two previous community‐based surveys elsewhere in Western Australia. However, at a lower cut‐off of 5 μg/dL, the prevalence of elevated lead levels was 24.6%, significantly higher than children tested in a previous Western Australian survey. The prevalence of blood lead levels of 10 μg/dL or greater in adults was 1.3% (26 adults), not significantly different from a previous Western Australian survey. Conclusions: The prevalence of preschool children with blood lead levels exceeding the current level of concern was not significantly increased. However, the increased prevalence of children with lead levels at or above 5 μg/dL demonstrates exposure to lead dust pollution. Implications: This episode of lead dust contamination highlights the need for strict adherence to environmental controls and effective monitoring processes to ensure the prevention of future events.